Exposição Universal 2015: luzes e sombras sobre a insegurança e a ajuda alimentar na Europa - Cristina Almeida Cunha Filgueiras (Ciências Sociais Unisinos)
The central purpose of this paper is to question the low visibility of food insecurity and food aid in the current European political context. At first, the reader is invited to a commented and critic visit to Milan 2015 Universal Exhibition. Also, it is demonstrated that food security and food aid remained in second plan in relation to other themes that rich countries prioritized to show the world. Then, the analysis of the main European Food Aid Program is able to demonstrate the social, political and economical relevance of the food insecurity problem in the continent and particularly in France. In second, the article examines the problems of poverty, food insecurity and waste of food in the European context. Third, it is mentioned the main European program of food aid, which existence shows the social, political and economic relevance of the problem in that continent. The case of France, one of the countries whose pavilion was one of the most visited in Milan 2015, which has a portion of its population living in food insecurity and assisted by food aid. Finally, three reasons for the scarce mention of those themes in the event in Milan are presented.